A best practices guide to CFD education in the undergraduate curriculum. (1st January 2014) - Eldredge, Jeff D.; Senocak, Inanc; Dawson, Paul; Canino, James; Liou, William W.; LeBeau, Ray; Hitt, Darren L.; Rumpfkeil, Markus P.; Cummings, Russell M.
The AIAA Fluid Dynamics Technical Committee formed a working group in 2010 to explore how to include computational fluid dynamics (CFD) in undergraduate education. The following article is the best practices guide resulting from that working group, and is intended to guide the development of CFD instructional content in undergraduate aerospace and mechanical engineering curricula. The article addresses a growing need for new engineers to become 'intelligent users' of CFD: that is, to be able to obtain a solution of a flow, and to critically assess the quality of the result. The article distils the concepts of CFD into curricular elements, and establishes reasonable expected outcomes for undergraduate-level instruction of these concepts. It then provides numerous case studies of existing CFD courses, presented in a hierarchy of various 'profiles' – from CFD light to CFD heavy – for inclusion in courses with lecture, laboratory or design formats. Specific needs of mechanical engineering programmes are also discussed. Hardware, software, and textbook resources are also briefly reviewed.